Sick sinus syndrome associated with topical timolol maleate instillation - Walia, Harpreet S. (Medknow Publications Pvt Ltd, 2011)
A 70-year-old black woman presented with intermittent palpitations and dyspnea was found to be bradycardic with a normal sinus rhythm. She had instilled her topical timolol maleate approximately 30 minutes prior to each of these episodes. Topical timolol was discontinued and the conduction abnormality resolved. She was diagnosed as having intermittent sinus bradycardia with intermittent atrioventricular block, likely induced by topical beta-blocker therapy. Topical timolol maleate is an effective treatment for ocular hypertension, acting by reducing aqueous fluid production. However, it can induce systemic side effects and should be used with caution in patients with, or predisposed to, cardiac or respiratory depression.